If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying A + 12 = 26 Reorder the terms: 12 + A = 26 Solving 12 + A = 26 Solving for variable 'A'. Move all terms containing A to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + A = 26 + -12 Combine like terms: 12 + -12 = 0 0 + A = 26 + -12 A = 26 + -12 Combine like terms: 26 + -12 = 14 A = 14 Simplifying A = 14
| -54+18=-4x+13x | | 81=9 | | 2(3x+5)+9=3x+34 | | 135=3y | | M/3+m/4=m/4 | | T=3a(ar+h) | | 161=7y | | 5-5=13x+7x | | 6y=114 | | 3n-14=17 | | 2x-10=7x+11 | | -2/5x=-6/25 | | 2x-10=7x+-1 | | 7/4t=-4/7 | | 0.4=-10z | | 4-14=-2z | | 2z=2.3+0.5 | | 22y=440 | | x^2+3xy+y^2=-16 | | 36x+60-14x+49=-2x-31 | | 40=12y-4y | | 3a+32=5a-4 | | -3/5z=9/20 | | 4/7x=4/5 | | 1/8y=-5 | | 10x^2-9x-4=0 | | 5x-3=3x+21+3x | | 5(x+8)=5 | | 1.41/2=x/10x | | .3x+12+1.5x=9 | | 3x+2.9=9.8 | | 8x^4-15x^2-2=0 |